Treatment Outcomes of Primary Bevacizumab Injection versus Primary Aflibercept Injection in Diabetic Macular Edema (Iraqi Journal of Medical Sciences, 2024)
Background: Visual impairment in diabetic retinopathy (DR) due to diabetic macular edema (DME) is common and disabling for increasing diabetic population all over the world. Varieties of anti-vascular endothelial growth factors (VEGF) had been developed to manage this problem.Objective: To observe and compare the short-term effect of intravitreal Bevacizumab (Avastin) and Aflibercept (Eylea) in patients with DME.Methods: A retrospective cross-sectional study was conducted to assess 40 eyes of 25 patients, 20 eyes received intravitreal Bevacizumab (1.25 mg in 0.05 ml) and the other 20 eyes received intravitreal Aflibercept (2 mg in 0.05 ml) as a line in treatment of diabetic macular edema from January 2022 to February 2024 in Dar-Alsalam Private Eye Hospital in Baghdad – Iraq. A baseline visual acuity (VA) and optical coherence tomography (OCT) were performed in the week prior to the 1st intravitreal injection and were repeated one month after the 3rd intravitreal injection.Results: The study sample involved 40 eyes of 25 patients, 15 of them were males and 10 were females and their ages ranged from 40-77 years (mean age 62.8 years). For Aflibercept group, the VA in log MAR (Mean±SD) showed a highly significant improvement from (0.5±0.39) to (0.31±0.38) after injection. In Bevacizumab group, the mean macular thickness significantly decreased from (458.92±107.1 µm) to (316.0±67.81 µm).Conclusion: Bevacizumab is more effective in decreasing macular thickness while Aflibercept is better in improving VA when treating diabetic macular edema.Keywords: Diabetic retinopathy, diabetic macular edema, Bevacizumab, AfliberceptCitation: Mahdi HA. Treatment outcomes of primary Bevacizumab injection versus primary Aflibercept injection in diabetic macular edema. Iraqi JMS. 2024; 22(2): 217-220. doi: 10.22578/IJMS.22.2.5
Keywords: Diabetic retinopathy; diabetic macular edema; Bevacizumab; Aflibercept